will use P (1 + r/2) ^2. Even though with these fact, they will have an exponent, and we must remove this exponent in order to get an accurate answer. Now we will set the formula up as (1 + r/2) * (1 + r/2). Because when we use the FOIL method we will be using the multiplication. Now we are going to use (A + B)*(C + D) = (1 + r/2)*(1 + r/2) where A = 1, B = r/2, C = 1, and D = r/2. Now we are now using A is multiplied by C, this actually comes down to me using 1 and then multiplied by 1 and the results…
Words 1035 - Pages 5